Intracavitary adoptive transfer of IL-12 mRNA-engineered tumor-specific CD8+ T cells eradicates peritoneal metastases in mouse models. (31st December 2023) - Di Trani, Claudia Augusta; Cirella, Assunta; Arrizabalaga, Leire; Bella, Ángela; Fernandez-Sendin, Myriam; Russo-Cabrera, Joan Salvador; Gomar, Celia; Olivera, Irene; Bolaños, Elizabeth; González-Gomariz, José; Álvarez, Maite; Etxeberria, Iñaki; et al.
ABSTRACT: Previous studies have shown that local delivery of tumor antigen-specific CD8 + T lymphocytes engineered to transiently express single-chain IL-12 mRNA is highly efficacious. Peritoneal dissemination of cancer is a frequent and often fatal patient condition usually diagnosed when the tumor burden is too large and hence uncontrollable with current treatment options. In this study, we have modeled intracavitary adoptive T cell therapy with OVA-specific OT-I T cells electroporated with IL-12 mRNA to treat B16-OVA and PANC02-OVA tumor spread in the peritoneal cavity. Tumor localization in the omentum and the effects of local T-cell encounter with the tumor antigens were monitored, the gene expression profile evaluated, and the phenotypic reprogramming of several immune subsets was characterized. Intraperitoneal administration of T cells promoted homing to the omentum more effectively than intravenous administration. Transient IL-12 expression was responsible for a favorable reprogramming of the tumor immune microenvironment, longer persistence of transferred T lymphocytes in vivo, and the development of immunity to endogenous antigens following primary tumor eradication. The efficacy of the strategy was at least in part recapitulated with the adoptive transfer of lower affinity transgenic TCR-bearing PMEL-1 T lymphocytes to treat the aggressive intraperitoneally disseminated B16-F10 tumor. Locoregional adoptive transfer of transiently IL-12-armored T cells appears to offer promising therapeutic advantages in terms of anti-tumor efficacy to treat peritoneal carcinomatosis.